The influence of chokeberry juice supplementation on the reduction of oxidative stress resulting from an incremental rowing ergometer exercise - Pilaczynska-Szczesniak, L.; Skarpanska-Stejnborn, A.; Deskur, E.; Basta, P.; Horoszkiewicz-Hassan, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
The aim of the study was to investigate the influence of an increased intake of anthocyanins, contained in chokeberry juice, on the redox parameters in rowers performing a physical exercise during a 1-month training camp. The athletes were randomly assigned to receive 150 mL of chokeberry juice daily, containing 23 mg/100 mL of anthocyanins (supplemented group), or placebo (control group). Before and after the supplementation period, the subjects performed an incremental rowing exercise test. Blood samples were taken from the antecubital vein before each exercise test, 1 min after the test, and following a 24-h recovery period. After the supplementation period, TBARS concentrations in the samples collected 1 min after the exercise test and following a 24-h recovery period were significantly lower in the subjects receiving chokeberry juice than in the control group. In the supplemented group, glutathione peroxidase activity was lower in the samples collected 1 min after the exercise test, and superoxide dismutase activity was lower in the samples taken following a 24-h recovery, as compared to the subjects receiving placebo. These findings indicate that an increased intake of anthocyanins limits the exercise-induced oxidative damage to red blood cells, most probably by enhancing the endogenous antioxidant defense system.